ВРАХУВАННЯ СПОЖИВАННЯ ЕЛЕКТРОЕНЕРГІЇ ЕНЕРГОЄМНИМИ ПІДПРИЄМСТВАМИ ПРИ КОРОТКОСТРОКОВОМУ ПРОГНОЗУВАННІ ЕЛЕКТРИЧНОГО НАВАНТАЖЕННЯ ЕНЕРГОСИСТЕМИ - Черненко, П.О.; Мартинюк, О.В.; Мірошник, В.О. (Інститут електродинаміки НАН України, Київ, 2014)
The paper demonstrates the benefits of metering electricity of intensive enterprises (IE) in solving the problem of shortterm forecasting of the total electrical load (TEL) of power system (PS). The modeling and forecasting of TEL PS based on using of artificial neural networks. The correctness of preparation of original data for the network training was provided preliminary statistical analysis of information. Decomposition of the total electrical load with the release in a separate component the loads of intensive enterprises allowed to improve mathematical models of influence on TEL of meteorological factors and improve the accuracy of the short-term forecasting TEL in the PS with a predominance of industrial load. References 3, tables 2, figures 2.